Adverse childhood experiences and its association with emotional and behavioral problems in U.S. children of Latino immigrants. (February 2021) - Rosado, Javier I.; Ramirez, Andrea; Montgomery, Jordan; Reyes, Elena; Wang, Yuxia
Abstract: Background: Research has long shown that Adverse Childhood Experiences (ACEs) are correlated with major risk factors for several of the leading causes of death in adults. However, only recently have studies begun to measure the impact of ACEs during childhood and on underserved populations. Objective: This study assessed the prevalence of 8 ACEs, including physical, emotional, and sexual abuse, among rural U.S. Latino children of immigrant parents. We examined the association of those adversities with several factors including emotional and behavioral difficulties, health problems and healthcare utilization. Participants and setting: A total of 100 Latino subjects (ages 8–17) were recruited from a community health center in Southwest Florida. Methods: Parents and children were asked to complete the Child Trust Events Survey to measure child ACEs; Parents were asked to complete the Strengths and Difficulties Questionnaire to measure child emotional and behavioral problems. Results: Child ACEs ranged from 1.38 (parent-report) to 1.56 (child self-report) with emotional abuse, incarceration, and loss/separation from a caregiver being the most common. ACEs were correlated with emotional symptoms (p = .038 for child-report; p = .043 for parent-report), hyperactivity/inattention problems (p = .011 for parent-report), and with total behavioral difficulties (p = .021 for parent-report). There was a negative correlation between ACES and child chronic health diagnosis (p = .038 for parent-report; p = .010 for child-report) and total health problems (p = .021). There was no significant relationship between ACEs and healthcare utilization. Conclusions: ACEs appear to be more prevalent among rural Latino youth in immigrant families and may be associated with emotional and behavioral problems during childhood.